Cardiac Magnetic Resonance with Delayed Enhancement of the Right Ventricle in patients with Left Ventricle primary involvement: diagnosis and evaluation of functional parameters. - Toia, Patrizia; Maffei, Erica; Mantini, Cesare; Runza, Giuseppe; La Grutta, Ludovico; Grassedonio, Emanuele; Guaricci, Andrea; Punzo, Bruna; Cavaliere, Carlo; Cademartiri, Filippo (Acta Biomedica Atenei Parmensis, 2022)
Cardiac Magnetic Resonance (CMR) allows an accurate Right Ventricle (RV) assessment that could be of great relevance in diseases causing inflammation or fibrosis. The aim of this study was to evaluate the concomitant involvement of the RV in patients with delayed enhancement (DE) of the Left Ventricle (LV-DE) using CMR.We retrospectively enrolled 95 (male n. 66; age 55±18years; BMI 26±5kg/m2) consecutive patients with LV-DE who underwent a CMR (Achieva 1.5 T, Philips) for different indications: post-ischemic dilated cardiopathy (PDM), hypertrophic cardiomyopathy (HCM), myocardial infarction (MI), myocarditis/pericarditis (MP) and congenital heart disease (CD). We assessed the presence and extension of DE and functional parameters such as ventricular end-diastolic (EDV), end-systolic volumes (ESV) and ejection fraction (EF) of both LV and RV.Prevalence of RV-DE was 30.5% (29/95): 75% (3/4) for CD, 44% (4/9) for PDM, 36% (17/47) for MI, 27.8% (5/18) for MP and 0% (0/17) for HCM. LV-EF and RV-EF were 53±15mL and 51±13mL, respectively, for patients without RV-DE (RV-DE-), and 40±19 mL and 42±15 mL, respectively, for patients with RV-DE (RV-DE+) (p